A 26-ppm/oC, 13.2-ppm/V, 0.11%-inaccuracy picowatt voltage reference with PVT compensation and fast startup. (September 2021) - Hu, Jinlong; Xu, Huachao; Wang, Jin; Liang, Ke; Lu, Chao; Li, Guofeng
Abstract: This paper proposes a picowatt voltage reference for Internet-of-Things applications, which require fast response speed and high insensitivity to variations of the process, supply voltage, and temperature (PVT). By employing a novel topology with a startup circuit and an effective PVT compensation method, the proposed voltage reference can achieve both high PVT stability and shorten the setup time. Based on a 0.18 μm standard CMOS process, post-layout simulation results show that the proposed design achieves a mean reference voltage of 755.6 mV with a variation coefficient of 0.11 % without trimming. The line regulation is 13.2 ppm/V over a supply voltage from 1 V to 1.8 V at 27 °C. The average temperature coefficient is about 26 ppm/°C in a temperature range from −20 °C to 120 °C. The 1 % settling time of the output reference voltage is about 274 μs.